Algorithms and the near future of design - Mills, Euan (Enquiry The ARCC Journal for Architectural Research, 2019)
Introduction by Silvio Carta In this article Euan Mills, who co-leads the Plantech programme at Connected Places Catapult, reflects on the changes of the design, planning and construction industries. The Connected Places Catapult is a centre devoted to the development and advancement of innovation in cities supported by the UK government. In this multidisciplinary team, planners, urban designers and many other experts collaborate with the public and private sectors, informing the design and construction industries as well as influencing policy-makers. In recent years, Euan and colleagues have been particularly active in engaging with academics, designers and the public in devising new ways in which the planning system in the UK can be improved and updated taking full advantage of new digital technologies and computational approaches to design increasingly available today. Under the title of Plantech (Connected Places Catapult 2019), Euan and colleagues are promoting a new planning agenda whereby in a near future urban data, people’s input and the regulatory system can converge into a seamless framework. Not only this would significantly simplify the planning system and the relationship that residents have with planning authorities and designers but, more importantly, it will synchronise some of the workflows that characterise urban planning and permissions (often with scanned version of old documents, historical paper archives etc.) with the digital assemblage of big data that is the fabric of our cities today.